The State, Business and Education: Public-Private Partnerships Revisited - Alexandra Draxler (NORRAG Series on International Education and Development, 2018)
Businesses, philanthropies and non-profit entities are increasingly successful in capturing public funds to support private provision of schooling in developed and developing countries. Coupled with market-based reforms that include weak regulation, control over workforces, standardization of processes and economies of scale, private provision of schooling is often seen to be convenient for both public authorities and businesses. This book examines how the public subsidization of these forms of private education affects quality, equality and the realization of human rights. With original research from leading experts, The State, Business and Education sheds light on the privatization of education in fragile circumstances. It illustrates the ways in which private actors have expanded their involvement in education as a business, and shows the influence of policy borrowing on the spread of for-profit education. Case studies from Argentina, Bangladesh, Brazil, China, India and Syrian refugee camps illustrate the ways in which private actors have expanded their involvement in education as a business. This book will be of interest not only to academics and students of international and comparative education, but also to education development professionals in both the private and public sectors, with its empirical assessment of case studies, and careful consideration of the lessons to be learned from each.